Openness of SME Operators towards Financial and Tax Reporting: A Perspective from the Theory of Planned Behavior - Stefani Fierzca Dewi; Apelina Teresia; M. Devitia Putri Nilamsari; Shandy Jannifer Matitaputty (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
Financial record-keeping and taxation have become strategic priorities amid the high investment opportunities in the Metropolitan City. MSMEs are prime examples of business entities reliant on funding accessibility. The importance of financial record-keeping and taxation for MSMEs hinges on the awareness and readiness of MSMEs operators. This study aims to achieve the following objectives: (1) Understand the perspectives of MSMEs operators in Semarang City regarding financial record-keeping, (2) Explore how MSMEs operators use financial information in their business decisions, and (3) Provide an overview of MSMEs operators' perspectives in Semarang City regarding taxation. The research employs a qualitative approach with semi-structured interviews and utilizes snowball sampling for data collection. Data analysis is conducted using NVIVO software, grounded in the Theory of Planned Behavior as the analytical framework. The study reveals that MSMEs in Semarang City consider financial record-keeping and taxation fundamental, yet the utilization of financial information by MSMEs operators remains suboptimal. Key challenges include insufficient understanding of proper financial record-keeping practices, irregular and undisciplined recording habits, limited proficiency in using modern technology, and a lack of ongoing training for MSMEs operators.